Comparative molecular dynamics simulations of thermal conductivities of aqueous and hydrocarbon nanofluids - Loya, Adil; Najib, Antash; Aziz, Fahad; Khan, Asif; Ren, Guogang; Luo, Kun (Beilstein Journal of Nanotechnology, 2022)
The addition of metal oxide nanoparticles to fluids has been used as a means of enhancing the thermal conductive properties of base fluids. This method formulates a heterogeneous fluid conferred by nanoparticles and can be used for high-end fluid heat-transfer applications, such as phase-change materials and fluids for internal combustion engines. These nanoparticles can enhance the properties of both polar and nonpolar fluids. In the current paper, dispersions of nanoparticles were carried out in hydrocarbon and aqueous-based fluids using molecular dynamic simulations (MDS). The MDS results have been validated using the autocorrelation function and previous experimental data. Highly concurrent trends were achieved for the obtained results. According to the obtained results of MDS, adding CuO nanoparticles increased the thermal conductivity of water by 25% (from 0.6 to 0.75 W·m−1·K−1). However, by adding these nanoparticles to hydrocarbon-based fluids (i.e., alkane) the thermal conductivity was increased three times (from 0.1 to 0.4 W·m−1·K−1). This approach to determine the thermal conductivity of metal oxide nanoparticles in aqueous and nonaqueous fluids using visual molecular dynamics and interactive autocorrelations demonstrate a great tool to quantify thermophysical properties of nanofluids using a simulation environment. Moreover, this comparison introduces data on aqueous and nonaqueous suspensions in one study.
Keywords: alkanes; aqueous solutions; CuO; hydrocarbon solutions; molecular dynamics simulation; nanoparticles; thermal conductivity